Adoption of a Personal Health Record in the Digital Age: Cross-Sectional Study - Yousef, Consuela Cheriece; Thomas, Abin; Alenazi, Ahmed O; Elgadi, Sumaya; Abu Esba, Laila Carolina; AlAzmi, Aeshah; Alhameed, Abrar Fahad; Hattan, Ahmed; Almekhloof, Saleh; AlShammary, Mohammed A; Alanezi, Nazzal Abdullah; Alhamdan, Hani Solaiman; et al. (JMIR Publications, 2020)
BackgroundAs health care organizations strive to improve health care access, quality, and costs, they have implemented patient-facing eHealth technologies such as personal health records to better engage patients in the management of their health. In the Kingdom of Saudi Arabia, eHealth is also growing in accordance with Vision 2030 and its National Transformation Program framework, creating a roadmap for increased quality and efficiency of the health care system and supporting the goal of patient-centered care. ObjectiveThe aim of this study was to investigate the adoption of the personal health record of the Ministry of National Guard Health Affairs (MNGHA Care). MethodsA cross-sectional survey was conducted in adults visiting outpatient clinics in hospitals at the Ministry of National Guard Health Affairs hospitals in Riyadh, Jeddah, Dammam, Madinah, and Al Ahsa, and primary health care clinics in Riyadh and Qassim. The main outcome measure was self-reported use of MNGHA Care. ResultsIn the sample of 546 adult patients, 383 (70.1%) reported being users of MNGHA Care. MNGHA Care users were more likely to be younger (P<.001), high school or university educated (P<.001), employed (P<.001), have a chronic condition (P=.046), use the internet to search for health-related information (P<.001), and use health apps on their mobile phones (P<.001). ConclusionsThe results of this study show that there is substantial interest for the use of MNGHA Care personal health record with 70% of participants self-reporting use. To confirm these findings, objective data from the portal usage logs are needed. Maximizing the potential of MNGHA Care supports patient engagement and is aligned with the national eHealth initiative to encourage the use of technology for high-quality, accessible patient-centered care. Future research should include health care provider perspectives, incorporate objective data, employ a mixed-methods approach, and use a theoretical framework.